Pengembangan Packaging Produk Untuk Menambah Nilai Jual Pada UMKM Minasarua Saijah Sondosia Kabupaten Bima - Awalia, Shafira; Wulandari; Gusmawarni; Julianti, Mihra; Purnama, Ita (LANCAH: Jurnal Inovasi dan Tren, 2024)
Micro businesses or small and medium enterprises (MSMEs) are one of the backbones of the Indonesian economy. The role of MSMEs is to meet people's needs for superior quality products, open new jobs and increase regional income. One of the micro businesses in Sondosia Village, Bima Regency is Minasarua Saijah, but its distribution is considered less widespread. The aim of this guidance is to develop Minasarua Saijah products in order to bring MSMEs up to class to increase sales results and distribution coverage. The implementation methods used are surveys, interviews, discussions and implementation. The results obtained from this activity are product changes to become superior, including packaging and logo innovations to increase consumer buying interest. From the results of the guidance carried out, it is hoped that Minasarua Saijah MSMEs can develop even more rapidly so that they can increase income.